THE EFFECT OF SBI INTEREST RATE, DEBT TO EQUITY RATIO, RETURN ON EQUITYAND EARNING PER SHARE ON STOCK RETURNSIN MANUFACTURING COMPANIES - Hiya, Nirmadarningsih; Hasyim, Diana; Muda, Iskandar; Soemitra, Andri; Sugianto (The journal of contemporary issues in business and government, 2021)
This study aims to determine the effect of Bank of Indonesia Certificate (SBI) Interest Rates, Debt to Equity Ratio (DER), Return On Equity (ROE), and Earning Per Share (EPS) on Stock Returns of Manufacturing Companies in the Food and Beverage Sub-sector listed on the Indonesia Stock Exchange. This research is all industries that areincluded in the food and beverage sub-sector manufacturing companies. The data used in this research is secondary data. The sampling technique was carried out using the purposive sampling method, namelyselecting samples based on specific criteria. The research sample was obtained from as many as ten companies from 2014 to 2018. The methods used in this research are descriptive statistics, classical assumption test (normality test, multicollinearity test, heteroscedasticity test, and autocorrelation test), multiple linear regression, coefficient of determination, and hypothesis testing (partially and simultaneously). The results of this study indicate that partially the SBI interest rate has a significant positive effect on stock returns, and Earning Per Share (EPS) has a significant positive effect on stock returns. Meanwhile, Debt to Equity Ratio (DER) and Return On Equity (ROE) have no significant effect on stock returns. Simultaneously the interest rates of SBI, DER, ROE, and EPS have a significant effect on stock returns.